“Os brasis estilizados” de dona terezinha: uma leitura histórica do município de Serra do Mel/RN (1970 - 1981) - Nogueira, Francisca Julimária Freire (Universidade Federal Rural do Semi-Árido, 2020)
This research aims to understand the municipality of Serra do Mel / RN in the light of the story told by those who lived it. Based on the historical reconstrutivo of the Municipality of Serra do Mel, Rio Grande do Norte, with emphasis on the period from 1970 to 1981. The methodology of this research consisted of reading: bibliographic material, data collection from digital collections, books, documents etc., field research with semi-structured interview. In order to understand some central concepts of this study, we spoke with Maurice Halbwaches about collective history, Antônio Carlos Gil where we talked about the methods and techniques of social research, Minayo, about research methodology. Still in the writings of Michael Pollak in his interpretation of collective memory and individual memory. We also spoke with Guimarães Neto on a sensitive basis in the treatment of the facts that were the narratives through oral reports, Walter Benjamin on the importance of the facts narrated as a work of artisan, and Michel de Certeau, among others. The research results were quite satisfactory, and made us realize how much the Human and Social Sciences have a fundamental role for society. It is these researches that point to a whole historical framework of changes, transformations, which had their social, cultural, political and economic moments.
Monografia
Keywords: Serra do Mel; Memórias; História; Educação do campo; Serra do Mel; Memoirs; History; Rural education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL